"And the BAFTA goes to […]": the assurance role of the auditor in the film awards ceremony. Issue 5 (2nd June 2014) - Jeacle, Ingrid
Abstract : Purpose: – The purpose of this paper is to examine the role of the Official Scrutineer in the annual film awards ceremony of the British Academy of Film and Television Arts (BAFTA), a role currently occupied by the audit firm Deloitte. The case of BAFTA provides an illustrative example of the increasing demand for discretionary assurance services from audit firms (Free et al., 2009), which in turn is reflective of Power's (1997) "audit society". It showcases the power of audit as a legitimating tool. The paper seeks to understand the role of the auditor as assurance provider by drawing upon Goffman's (1959) dramaturgical framework. Viewing the auditor as "performer" and a range of interested stakeholders (BAFTA voting members, sponsors, award winners and industry commentators) as the "audience", this theoretical lens facilitates insights into the nature of assurance provision. Design/methodology/approach: – The paper gathers interview data from within the case organization (BAFTA), it's Official Scrutineers (Deloitte), BAFTA voting members, sponsors, award winners and film industry commentators. Findings: – Drawing on Goffman's (1959) work on impression management to inform its theoretical argumentation, the analysis of results from 36 interviews indicates that Deloitte are highly effective in delivering a successful performance to their audience; they convey a very convincing impression of trust and assurance. The paper therefore suggests the importance of performance ritual in the auditor's role as assurance provider. Additionally, it argues that such a performance may be particularly effective, in the eyes of the audience, when played by a well known audit firm. Originality/value: – The paper highlights the expanding territorial scope of assurance provision by audit firms. By focusing on a glamorous media event, it also furthers an understanding of the role of accounting within the domain of popular culture.